Three case studies of community behavioral health support from the US Department of Veterans Affairs after disasters - Tamar Wyte-Lake; Susan Schmitz; Reginald J. Kornegay; Felix Acevedo; Aram Dobalian (BMC, 2021)
Abstract Background Community disaster resilience is comprised of a multitude of factors, including the capacity of citizens to psychologically recover. There is growing recognition of the need for public health departments to prioritize a communitywide mental health response strategy to facilitate access to behavioral health services and reduce potential psychological impacts. Due to the US Department of Veterans Affairs' (VA) extensive experience providing trauma-informed behavioral healthcare to its Veterans, and the fact that VA Medical Centers (VAMCs) are located throughout the United States, the VA is well situated to be a key partner in local communities' response plans. In this study we examined the role the VA can play in a community's behavioral health response using case studies from three disasters. Methods This study investigated experiences of VA employees in critical emergency response positions (N = 17) in communities where disasters occurred between 2017 and 2019. All respondents were interviewed March-July 2019. Data were collected via semi-structured interviews exploring participants' experiences and knowledge about VA activities provided to communities following the regional disasters. Data were analyzed using thematic and grounded theory coding methods. Results Respondents underscored VA's primary mission after a disaster was to maintain continuity of care to Veterans. The majority also described the VA supporting community recovery. Specifically, three recent events provided key examples of VA's involvement in disaster behavioral health response. Each event showed VA's integration into local response structures was facilitated by pre-existing emergency management and clinical relationships as well as prioritization from VA leadership to engage in humanitarian missions. The behavioral health interventions were provided by behavioral health teams integrated into disaster assistance centers and non-VA hospitals, VA mobile units deployed into the community, and VA telehealth services. Conclusions Recent disasters have revealed that coordinated efforts between multidisciplinary agencies can strengthen communities' capacity to respond to mental health needs, thereby fostering resilience. Building relationships with local VAMCs can help expedite how VA can be incorporated into emergency management strategies. In considering the strengths community partners can bring to bear, a coordinated disaster mental health response would benefit from involving VA as a partner during planning.